Flowers in Classical Malay Literature: A Study of Aesthetics: (Bunga dalam Kesusasteraan Melayu: Satu Kajian Estetika) (Malay Literature, 2021)
Flowers are among God's amazing creations in the mortal world. There are a variety of flowers in the Malay world, such as the hibiscus, various types of jasmine and the lotus. These flowers are recorded in old Malay texts. Therefore, this paper examines flowers in traditional or classical Malay literature as elements employed, mentioned or used metaphorically for a specific purpose, which clearly shows the wisdom of the Malays of old. The methodology employed for this study was library research as well as textual analysis to analyse relevant data. A conceptual framework related to literary aesthetics was used as the basis of the study. The study finds that in Malay texts, flowers are used for both their figurative and literal meanings. This study is important in demonstrating the ingenuity of the Malays.Keywords: flowers, aesthetics, symbolism, literal, ingenuity